SARO-SARO: RELEVANCE OF CUSTOM SYMBOLS AND THE PROHIBITION OF HIJAB IN MUSLIM COMMUNITY WEDDINGS IN JAILOLO SELATAN DISTRICT, WEST HALMAHERA REGENCY - Abu Sahman Nasim; Nur Azizah Rahman; Iin Junisti Hamid (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
This article explores the Saro-saro tradition in the marriage of the Jailolo Muslim Society. In this tradition, traditional symbols should be obeyed, such as the use of conventional clothing, a headscarf bun as a standard symbol, and the prohibition of wearing hijab. This research is qualitative research with an ethnographic approach. Research findings show the ban on head coverings or hijabs and the use of buns as a symbol of tradition, even though they wear hijabs daily. The obligation to wear a bun rule out the obligation to wear a hijab for a Muslim woman at a wedding. Implementing saro-saro is a traditional ritual classified as mubah (allowed) to be applied; merely the conventional symbol, which needs a bun for saro for those who wear hijab, is contrary to Islamic law. When the traditional provision and Islamic law provisions are contradictory, it is a must to negotiate and dialogue then preempt the main requirements on the philosophy of